Crystalline silicon on glass—interface passivation and absorber material quality. (4th November 2015) - Gabriel, Onno; Frijnts, Tim; Preissler, Natalie; Amkreutz, Daniel; Calnan, Sonya; Ring, Sven; Stannowski, Bernd; Rech, Bernd; Schlatmann, Rutger
Abstract: Thin crystalline silicon solar cells prepared directly on glass substrates by means of liquid‐phase crystallization of the absorber utilize only a small fraction of the silicon material used by standard wafer‐based silicon solar cells. The material consists of large crystal grains of up to square centimeter area and results in solar cells with open‐circuit voltages of 650 mV, which is comparable with results achieved with multi‐crystalline silicon wafers. We give a brief status update and present new results on the electronic interface and bulk properties. The interrelation between surface passivation and additional hydrogen plasma passivation is investigated for p‐type and n‐type absorbers with different doping concentrations. Internal quantum efficiency measurements from both sides on bifacial solar cells are used to extract the bulk‐diffusion length and surface‐recombination velocity. Finally, we compare various types of solar cell devices based on 10 µm thin crystalline silicon, where conversion efficiencies of 11–12% were achieved with p–type and n‐type liquid‐phase crystallized absorbers on glass. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Thin crystalline silicon solar cells prepared directly on glass substrates by means of liquid‐phase crystallization of the absorber utilize only a small fraction of the silicon material used by standard wafer‐based silicon solar cells. The influence of hydrogen plasma passivation and surface passivation of thin crystalline silicon absorbers were investigated for various p‐type and n‐type solar cells. The paper finishes with an outline of the perspectives and limits of this next‐generation solar cell technology.